Charge trapping properties and retention time in amorphous SiGe/SiO2 nanolayers - Vieira, E. M. F. (2013)
In this paper, we report on the electrical properties of metal–oxide–semiconductor (MOS) capacitors containing a well-confined 8 nm-thick SiGe amorphous layer (a-SiGe) embedded in a SiO2 matrix grown by RF magnetron sputtering at a low temperature (350 ºC). Capacitance–voltage measurements show that the introduction of the SiGe layer leads to a significant enhancement of the charge trapping capabilities, with the memory effect and charge retention time larger for hole carriers. The presented results demonstrate that amorphous floating-gate SiGe layers embedded in SiO2 may constitute a suitable alternative for memory applications.